Hadith Study About Science - Uus Husni Hoer; Ainur Awaliah; Ingeu Siti Aisyah; Risma Euis Patonah (Penerbit Hellow Pustaka, 2026)
In the life of the world, science has a very important role. The development and progress of science provides convenience for life, both in individual life and in society. In addition to the Qur'anic verses that position knowledge and knowledgeable people, the Qur'an also encourages Muslims to pray for knowledge. It is in this connection that the concept of reading, as one of the means of increasing knowledge, becomes very important and Islam has from the beginning emphasized the importance of reading. Seeking and demanding knowledge is an obligation for a Muslim, both men and women. The Messenger of Allah SAW made the activity of demanding knowledge and knowledge needed by Muslims to uphold their religious affairs, as an obligation that is Fardlu 'Ain for every Muslim. Fardlu Ain knowledge is knowledge that everyone who has reached the age of aqil baligh is obliged to practice it which includes the science of aqidah, doing Allah's commands, and leaving His prohibitions.